Preventing Thotraa Noigal in the Neoteric Community Through Ethics and Codes of Conducts Relevant to Siddha and Formation of Stress Relieved. Society Through Spiritual Performance -A Literature - Sathiyaseelan, V.; Thillany, P.V. (World Journal of Pharmaceutical Research, 2019)
In the modern age when we are in an indiscriminate race of industrialization and urbanization, we are going ahead with unnatural way of living life. Consequently the human health is constantly deteriorating. This induces "Prevention is better than cure". The high end of medical science is the preservation of health and can be attained in two ways. Firstly by eradicating diseases which may invade the body and secondly by due to observation of such rules that would keep away diseases. These rules are no less important than the treatment of diseases and the methods of cure. The rules in respect of food and exercise by observing which a person succeeds in maintaining normal health constitute that branch of medical science, which is called hygiene. With respect to that, certain preventive measures (1) Food habbits and ethics, (2) Mind and spiritual wellbeing, (3) Social behavior and discipline, (4) Social relationship, (5) Prevention of alcoholics and gambling, (6) Awareness of sexual life are analyzed in the tamil literary ancient texts Aacharakkovai, Thirikadugam, Elathi, Sirupanjamoolam, Thirukkural and in Saiva Siddhanta text Tirumandiram to state the major problem that prevails in the modern society middle and old aged community that are affected by thotraa noigal. The analytical study will render the knowledge to bringout the philosophical perspectives into action to avoid affected by such diseases. The authors of these texts too justify their views through religious and practical life in concern to healthy and spiritual wellbeing in orderly relieving the mankind from disease proning through yoga therapy and meditation. Thus the idea could be attained by the good social behaviors and relationships will guide a good social understanding to lead a diseaseless life. This social concern and community related medical advises are over ruled in these texts.
Keywords: Preventive measures; Ancient texts; Thotraa noigal; Social concern